Persepsi Guru Bahasa Inggris Terhadap Multimedia Pembelajaran Interaktif dan Pembelajaran Terdiferensiasi - Arif Bulan; Ismail; M. Nur Imansyah; Hasan; Supriyaddin (CV. Multi Kreasi Media, 2023)
English teachers' perceptions of interactive learning multimedia and differentiated learning are important to know, considering that they are part of the independent curriculum. This study aims to find out English teachers' perceptions of interactive learning multimedia and to find out English teachers' perceptions of differentiated learning. The method used in this research is qualitative research. The respondents of this research were 22 English teachers. The data analysis in this study used descriptive analysis. The result of this study shows that (1) there are still many teachers who have not made interactive learning media multimedia, (2) there are still many teachers who have not participated in training or workshops on making interactive learning multimedia, (3) there are still many teachers who have not made learning materials based on differentiated learning principles, (4) and there are still many teachers who have not participated in training on making differentiated learning materials. Thus, the recommendation from this study is that there is a need for training or workshops on making interactive learning multimedia and differentiated learning for English teachers in Dompu district organized by the local education office, the English subject teachers' meeting (MGMP), or higher education institutions (campus/university).